2012
DOI: 10.1111/j.1365-2427.2012.02825.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of water level on macrophyte growth and trophic interactions in eutrophic Mediterranean shallow lakes: a mesocosm experiment with and without fish

Abstract: Summary 1. Water‐level fluctuations are typical of lakes located in the semi‐arid Mediterranean region, which is characterised by warm rainy winters and hot dry summers. Ongoing climate change may exacerbate fluctuations and lead to more severe episodes of drought, so information on the effects of water level on the functioning of lake ecosystems in such regions is crucial. 2. In eutrophic Lake Eymir, Turkey, we conducted a 4‐month (summer) field experiment using cylindrical 0.8‐m‐ (low‐water‐level) and 1.6‐m‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 45 publications
7
38
0
1
Order By: Relevance
“…Moreover, the simultaneous increases in both WL and Secchi depth in 2009 and 2013 may explain the lack of changes in macrophyte coverage. Our results corroborate those of previous monitoring and experimental studies in Turkish lakes, showing that the water level overrides the effects of the turbid water conditions [39][40][41]52]. The CIT analysis revealed that not only water depth but also water clarity are critical factors for determining macrophyte growth in Lake Eymir.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the simultaneous increases in both WL and Secchi depth in 2009 and 2013 may explain the lack of changes in macrophyte coverage. Our results corroborate those of previous monitoring and experimental studies in Turkish lakes, showing that the water level overrides the effects of the turbid water conditions [39][40][41]52]. The CIT analysis revealed that not only water depth but also water clarity are critical factors for determining macrophyte growth in Lake Eymir.…”
Section: Discussionsupporting
confidence: 90%
“…This is supported by an increase in macrophyte abundance as evidenced by the enhanced proportion of periphytic diatoms and of both macrophyte-and sedimentassociated cladocerans, with potential positive feedback on water clarity via reduced phytoplankton development, as seen in other studies (e.g. Coops et al, 2003;Bucak et al, 2012;Jeppesen et al, 2015). Accordingly, a decline in the proportion of planktonic diatom forms suggests a reduction in phytoplankton production and improved water clarity.…”
Section: Discussionsupporting
confidence: 58%
“…Two recent mesocosm studies undertaken in warm Turkish shallow lakes located in a semi-arid dry climate with major water level fluctuations (Ö zkan et al, 2010;Bucak et al, 2012) have shown greater resistance by macrophytes to nutrient loading owing to major water level reduction than expected from studies of northern temperate lakes. A mesocosm experiment conducted in eutrophic Lake Eymir with two water depths, 0.8 m and 1.6 m, showed that the strongest macrophyte growth occurred in the low water level fishless mesocosms (Bucak et al, 2012).…”
Section: Effects Of Changes In Water Level On Biotamentioning
confidence: 99%
“…A mesocosm experiment conducted in eutrophic Lake Eymir with two water depths, 0.8 m and 1.6 m, showed that the strongest macrophyte growth occurred in the low water level fishless mesocosms (Bucak et al, 2012). However, despite high nutrient concentrations and low water clarity, macrophytes were also abundant in the fish mesocosms and abundance increased further following a water level decrease from midsummer onwards.…”
Section: Effects Of Changes In Water Level On Biotamentioning
confidence: 99%